Analisis Rasio Profitabilitas, Likuiditas, dan Solvabilitas dalam Mengukur Kinerja Keuangan pada Koperasi Karyawan BUMN di Palembang Periode 2016-2018 (Studi Kasus Kopkar PUSRI & Kopkar Semen Baturaja) - Reny Aziatul Pebriani; Shinta Dwina Ramdhani S. (Universitas Indo Global Mandiri)
This study aims to analyze the financial performance of PT PUSRI Palembang Employees' Cooperative and the Semen Baturaja Palembang Employees' Cooperative (KOPKAR) using profitability, liquidity, and solvency ratios compared to standard ratios based on State Ministerial Regulations for Cooperatives and Small and Medium Enterprises Republic of Indonesia No.18/Dep.I/XI/2018. This research collected quantitative secondary data obtained from documentation, interviews, and literature studies. The results showed that the profitability level of the Employees' Cooperative of PUSRI and Semen Baturaja in 2016-2018 in terms of net profit margin was poor. In terms of return on assets, the performance of the two cooperatives was poor. In terms of return on equity, the Employees's Cooperative of PUSRI was fair, whereas Employees' Cooperative of Semen Baturaja was poor. The liquidity level of the Employees' Cooperative was fair, and the Employees' Cooperative of Semen Baturaja was good. On the other hand, the level of solvency in 2016-2018, the debt to assets ratio evidenced that both of the employees' cooperative performance was both fair.